Warfarin, head injury and bruising - Wallace, Marc (BMJ Publishing Group, 2010)
A 75-year-old woman with a history of recurrent pulmonary emboli and atrial fibrillation presented with shortness of breath. Her warfarin had been stopped 4 weeks previously after a minor fall where a head injury and extensive facial “bruising” was noted. A computed tomography pulmonary angiogram subsequently confirmed another pulmonary embolus. On examination the discolouration was still evident, but it was noted to be in a photosensitive distribution, and on further questioning it was determined that it had been present for some months before the fall. The patient had been on minocycline for acne rosacea for several years and the diagnosis of minocycline induced hyperpigmentation allowed for a more considered decision to restart warfarin.